As televisões e o prolongamento do acontecimento: o Caso Quinta da Fonte - Sebastião, Claudia Domingues (2011)
Submitted by Bruno Marçal (bruno.marcal@iscte.pt) on 2011-04-12T11:22:56Z No. of bitstreams: 4 Resumo tese Claudia Sebastião.pdf: 51257 bytes, checksum: 4018f0481b84b7d179a5d5c67f60f34b (MD5) lombada tese claudia sebastião.pdf: 41545 bytes, checksum: b87ab278ddc3bc21db28b652a854e5f0 (MD5) corpo tese Claudia Sebastião.pdf: 1257183 bytes, checksum: 563c5072beff395c2ca35a316a273a65 (MD5) capa tese claudia sebastião.pdf: 176766 bytes, checksum: 1e5e4ad06c49cebb8f2f8ffb78590e68 (MD5)